A case report about anatomy applications for a physical therapy hybrid online curriculum. - Havens, Kathryn L.; Saulovich, Nicole A.; Saric, Karin J. (Journal of the Medical Library Association, 2020)
Background: Three-dimensional digital anatomy applications can provide a powerful supplement to more traditional learning modalities. The challenge for medical libraries and educators is to select an app that best supports anatomical learning objectives and then effectively integrate it into health sciences curricula. App selection is particularly important when traditional learning modalities, such as cadaver dissection, are not feasible. Selection was a challenge at the authors' university, as the doctor of physical therapy (DPT) program expanded into a hybrid online environment. Case Presentation: Reported here are our: (1) analysis and identification of an anatomy app to supplement cadaver lab instruction for DPT students who were enrolled in a hybrid program, where the majority of instruction took place online; (2) description of the implementation process; and (3) discussion of student feedback and the library's perspective. Features and shortcomings of two anatomy apps, Complete Anatomy (CA) 2019 by 3D4 Medical and Human Anatomy Atlas (HAA) 2019 by Visible Body, were reviewed. CA was selected based on smoother navigation, visually appealing graphics, and user customization tools. The library purchased 1,000 CA redemption codes as a pilot program. Video recordings and live demonstrations of the app were used for instruction. Student feedback indicated extensive use. Based on success of the pilot, the library will purchase additional licenses. Conclusions: Medical libraries can use our experience as an example to help select anatomy resources that would be useful when considering the conversion of health sciences programs into online environments and further guide app integration to supplement other anatomical models.